Combustión catalítica de compuestos orgánicos volátiles clorados - Rivera de la Rosa, Javier; Barresi, Antonello A. (UANL. Facultad de Ingeniería Mecánica y Eléctrica, 2002)
The combustion of chlorinated volatil organic compounds (VOCs) over the perovskites LaFeO3 and La0.9MnO3 catalysts were investigated by employing a monolithic reactor. The two catalysts were individuated from a preliminary screening to test the stability and the influence of nonstoichiometry; a dip coating technique for supporting powder catalyst; was developed and the prepared catalysts were tested in a monolithic reactor. It was studied the catalytic activity of different loadings of perovskite supported on the monolith and was compared the highest loadings with a commercial catalyst, the perovskites resulted efficient catalysts for combustion of aromatic and chlorinated VOCs.